A method for treating magnesium alloy by chemically forming a phosphorus-free and chromium-free film
Through the phosphorus-free and chromium-free film decomposition treatment method, the problem of increasing the surface thickness and color of magnesium alloys caused by the traditional physical sealing method is solved, and the stable and environmentally friendly magnesium alloy surface treatment is achieved, which improves the precision of the product and paint adsorption effect of the product .
Patent Information
- Application Number
- CN202310054224.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-03
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-02-03
AI Technical Summary
The existing magnesium alloy surface treatment method adopts the traditional physical closure method, which easily increases the thickness and color of the workpiece surface and is unstable in performance.
A phosphorus-free and chromium-free membrane decomposition treatment method is adopted, including degreasing, activation of pore expansion, surface conditioning and membrane decomposition steps, and is processed by adjusting pH and temperature, and finally baked in the oven to form a dense passivation film.
This method does not increase the thickness and color of the workpiece, improves the precision of the product, forms a stable passivation film, has self-repairability, improves the paint adsorption effect, and is environmentally friendly and suitable for environmental protection requirements.
Smart Images

Figure CN116219421B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium alloy film formation, in particular to a phosphorus-free and chromium-free film formation treatment method for magnesium alloy. Background Art
[0002] In view of the environmental protection requirements of the NB industry, in the past two years all customers have gradually introduced water-based paints and changed chemical solutions to phosphorus-free and chromium-free solutions. In addition, many parts of mainstream notebook computer brands have been changed from magnesium-aluminum molding to aluminum skin + magnesium-aluminum bracket bonding design.
[0003] During this process, the failure frequency of coating test has gradually increased. Each manufacturer has conducted separate analysis and verification on some factors such as the coating solution manufacturer, chemical process conditions, and the impact of the product appearance after coating on the paint.
[0004] Film formation refers to the process of metal surface being inactive or passivated by strong oxidants or electrochemical methods. It is a method of transforming the metal surface into a state that is not easily oxidized, thereby delaying the corrosion rate of the metal.
[0005] Most of the existing magnesium alloys are surface treated by traditional physical sealing method, which easily increases the thickness of the workpiece surface, the color of the cover workpiece, and the performance of the workpiece is unstable. Summary of the invention
[0006] The purpose of the present invention is to provide a phosphorus-free and chromium-free film chemical treatment method for magnesium alloys, so as to solve the problem that in the prior art, most magnesium alloys are surface treated by traditional physical sealing methods, which easily increase the thickness of the workpiece surface, the color of the cover plate workpiece, and the performance of the workpiece is unstable.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for forming a phosphorus-free and chromium-free film of a magnesium alloy, comprising the following steps:
[0008] S1, degreasing magnesium parts:
[0009] Place the magnesium parts in a degreasing tank, add a degreasing agent, adjust the pH to 12-14, degrease, then take out the magnesium parts, place them in the first water tank, adjust the pH to 6-13, wash them with water at room temperature for 60±5s, then transfer them to the second water tank, adjust the pH to 6-11, and wash them with water at room temperature for 60±5s;
[0010] S2, activation and hole expansion of magnesium parts:
[0011] Place the magnesium piece in an activation pore-expanding tank, add an activation pore-expanding agent, adjust the pH to 2-4, perform activation pore-expanding, then take out the magnesium piece, place it in the first water tank, adjust the pH to 3-7, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 5-7, and wash it with water at room temperature for 60±5s;
[0012] S3, adjust the magnesium parts:
[0013] Place the magnesium piece in a surface conditioning tank, add a surface conditioning agent, the mass percentage of the surface conditioning agent to water is 20% and 80%, adjust the pH to 9.5-10.5, perform surface conditioning twice, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-10, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-9, and wash it with water at room temperature for 60±5s;
[0014] S4, film formation:
[0015] Place the magnesium piece in a film forming tank, add a film forming agent, adjust the pH to 5.5-7.5, perform film forming, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-8, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-8, and wash it with water at room temperature for 60±5s;
[0016] S5, baking:
[0017] Place the magnesium piece in the oven, raise the temperature to 130±10℃, and bake for 1200-1500s.
[0018] Preferably, the degreasing agent is an alkaline degreasing agent, and the mass percentages of the degreasing agent and water in the degreasing tank are 15% and 85%.
[0019] Preferably, the degreasing temperature is 60±5° C., and the degreasing time is 300±5 s.
[0020] Preferably, the mass percentages of the activated pore expanding agent and water in the pore expanding groove are 10% and 90%.
[0021] Preferably, the temperature of the activation expansion is 40±5°C and the time is 180±5s.
[0022] Preferably, the temperature of the table adjustment is 65±5°C, and the time of a single table adjustment is 300±5s.
[0023] Preferably, the film forming temperature is 45±5° C. and the time is 240-300 s.
[0024] Preferably, the degreasing agent includes sodium silicate nonahydrate, sodium hydroxide, sodium gluconate and potassium silicate; the activating pore-enlarging agent includes citric acid, lactic acid and tert-octylphenyl polyoxyethylene ether.
[0025] Preferably, the surface conditioning agent includes sodium carbonate, sodium bicarbonate, sodium gluconate, potassium sodium tartrate, sodium lactate and tetrasodium ethylenediaminetetraacetate.
[0026] Preferably, the film forming agent includes citric acid, sodium metavanadate, ammonium acetate, sodium hydroxide and benzotriazole.
[0027] The present invention has at least the following beneficial effects:
[0028] (1) The phosphorus-free and chromium-free film chemical treatment method for magnesium alloy provided by the present invention has the characteristics of absolutely not increasing the thickness of the workpiece and changing the color, and improving the precision of the product compared with the traditional physical sealing method;
[0029] (2) The present invention provides a method for treating a magnesium alloy by chemically forming a phosphorus-free and chromium-free film. During the chemical forming process, a dense passivation film is formed on the surface of the product. The film has stable performance and can self-repair in the air.
[0030] Passivated surfaces are more stable;
[0031] (3) The present invention provides a method for treating a magnesium alloy by chemically forming a phosphorus-free and chromium-free film. After activation, pore expansion and surface conditioning, the film is chemically formed, and the paint adsorption effect is good, and the 100-grid test effect is improved;
[0032] (4) The present invention provides a method for treating a magnesium alloy by chemically treating a phosphorus-free and chromium-free coating. The chemical solution formula is phosphorus-free and chromium-free, and does not contain other heavy metals. It is an environmentally friendly and degradable process. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a surface observation diagram of the magnesium alloy before treatment in the present invention;
[0034] Figure 2 This is a surface observation diagram of the magnesium alloy after degreasing and surface conditioning treatment in the present invention;
[0035] Figure 3 This is a surface observation diagram of the magnesium alloy after film formation in the present invention;
[0036] Figure 4 This is a surface observation diagram of the magnesium alloy after the conversion film in the present invention;
[0037] Figure 5 is a flow chart of the present invention;
[0038] Figure 6 This is a Dyne pen test diagram in the present invention;
[0039] Figure 7 for Figure 6 An enlarged schematic diagram of the middle 70;
[0040] Figure 8This is a water drop angle test diagram of the first sample in the present invention;
[0041] Fig. 9 This is a water drop angle test diagram of the second sample in the present invention;
[0042] Fig.10 This is the hundred-grid test chart in the present invention. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example
[0045] A method for treating a magnesium alloy by chemically forming a phosphorus-free and chromium-free film, comprising the following steps:
[0046] S1, degreasing magnesium parts:
[0047] Place the magnesium piece in a degreasing tank, add a degreasing agent, the mass percentage of the degreasing agent and water in the degreasing tank is 15% and 85%, adjust the pH to 12-14, raise the temperature to 60±5℃, maintain the constant temperature for 300±5s, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-13, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-11, and wash it with water at room temperature for 60±5s;
[0048] Among them, degreasing agents include sodium silicate nonahydrate, sodium hydroxide, sodium gluconate and potassium silicate;
[0049] S2, activation and hole expansion of magnesium parts:
[0050] Place the magnesium piece in an activation hole expansion tank, add an activation hole expansion agent, the mass percentage of the activation hole expansion agent to water is 10% and 90%, adjust the pH to 2-4, raise the temperature to 40±5°C, maintain the constant temperature for 180±5s, then take out the magnesium piece, place it in the first water tank, adjust the pH to 3-7, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 5-7, and wash it with water at room temperature for 60±5s;
[0051] Wherein, the activated pore-enlarging agent includes citric acid, lactic acid and tert-octylphenyl polyoxyethylene ether;
[0052] S3, adjust the magnesium parts:
[0053] Place the magnesium piece in a surface conditioning tank, add a surface conditioning agent, the mass percentage of the surface conditioning agent to water is 20% and 80%, adjust the pH to 9.5-10.5, perform surface conditioning twice, the surface conditioning temperature is 65±5℃, and the time of a single surface conditioning is 300±5s, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-10, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-9, and wash it with water at room temperature for 60±5s;
[0054] Among them, the surface conditioning agents include sodium carbonate, sodium bicarbonate, sodium gluconate, potassium sodium tartrate, sodium lactate and tetrasodium EDTA;
[0055] S4, film formation:
[0056] Place the magnesium piece in a film forming tank, add a film forming agent, the mass percentages of the film forming agent and water are 10.8% and 89.2% respectively, adjust the pH to 5.5-7.5, raise the temperature to 45±5°C, maintain the constant temperature for 240-300s, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-8, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-8, and wash it with water at room temperature for 60±5s;
[0057] Among them, the film forming agents include citric acid, sodium metavanadate, ammonium acetate, sodium hydroxide and benzotriazole.
[0058] S5, baking:
[0059] Place the magnesium piece in the oven, raise the temperature to 130±10℃, and bake for 1200-1500s.
[0060] The surface of the product prepared in the above embodiment was observed. Figure 1-4 As shown, there are a lot of defects, oxides and dirt on the surface of magnesium alloy before treatment; after degreasing and surface conditioning, the surface is completely clean; when the film is formed, a dense passivation film is formed on the surface; after the film is converted, the adsorption effect of paint is good.
[0061] The surface of the film product obtained in the above embodiment was inspected and tested, and the results are as follows:
[0062] 1. White appearance:
[0063] The chemical film surface, curved surface and structural surface of magnesium parts all have varying degrees of surface mottling and whitening. This is mainly caused by molding broth flow marks, poor surface burning, and molding release agents and CNC cutting fluids adsorbed on the product surface.
[0064] 2. Surface tension test:
[0065] Dyne pen test, 66OK, 70NG, such as Figure 6-7 shown.
[0066] 3. Water drop angle test:
[0067] The water drop angle test data varies due to the surface smoothness of the mold, the degree of ABB grinding, the different grinding areas of large and small parts, and the water absorption of the film itself.
[0068] like Figure 8-9 As shown, two samples were selected for testing, and the test results of the water drop angles of the two samples were 15.53° and 19.99°, respectively, both within 20°, indicating that the water absorption is stronger, which is conducive to the adsorption of water-based paint.
[0069] 4. 100-grid test on the membrane surface:
[0070] The test results of 100 grids are all 5BOK, and there is no difference in the effect of 100 grids. In terms of 3M tape adhesion, the product has strong adhesion to the tape, such as Fig.10 shown.
[0071] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for treating a magnesium alloy by chemically treating a phosphorus-free and chromium-free film, characterized in that: The following steps are involved: S1, degreasing magnesium parts: Place the magnesium parts in a degreasing tank, add a degreasing agent, adjust the pH to 12-14, degrease, then take out the magnesium parts, place them in the first water tank, adjust the pH to 6-13, wash them with water at room temperature for 60±5s, then transfer them to the second water tank, adjust the pH to 6-11, and wash them with water at room temperature for 60±5s; The degreasing agent includes sodium silicate nonahydrate, sodium hydroxide, sodium gluconate and potassium silicate; the activating pore-enlarging agent includes citric acid, lactic acid and tert-octylphenyl polyoxyethylene ether; The mass percentages of the degreasing agent and water in the degreasing tank are 15% and 85%; S2, activation and hole expansion of magnesium parts: Place the magnesium piece in an activation pore-expanding tank, add an activation pore-expanding agent, adjust the pH to 2-4, perform activation pore-expanding, then take out the magnesium piece, place it in the first water tank, adjust the pH to 3-7, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 5-7, and wash it with water at room temperature for 60±5s; The mass percentages of the activated pore-enlarging agent and water in the pore-enlarging groove are 10% and 90%; S3, adjust the magnesium parts: Place the magnesium piece in a surface conditioning tank, add a surface conditioning agent, the mass percentage of the surface conditioning agent to water is 20% and 80%, adjust the pH to 9.5-10.5, perform surface conditioning twice, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-10, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-9, and wash it with water at room temperature for 60±5s; The surface conditioning agents include sodium carbonate, sodium bicarbonate, sodium gluconate, potassium sodium tartrate, sodium lactate and tetrasodium ethylenediaminetetraacetate; S4, film formation: Place the magnesium piece in a film forming tank, add a film forming agent, adjust the pH to 5.5-7.5, perform film forming, then take out the magnesium piece, place it in the first water tank, adjust the pH to 6-8, wash it with water at room temperature for 60±5s, then transfer it to the second water tank, adjust the pH to 6-8, and wash it with water at room temperature for 60±5s; The film forming agent includes citric acid, sodium metavanadate, ammonium acetate, sodium hydroxide and benzotriazole; S5, baking: Place the magnesium piece in the oven, raise the temperature to 130±10℃, and bake for 1200-1500s.
2. The method for treating a magnesium alloy by forming a phosphorus-free and chromium-free film according to claim 1, characterized in that: The degreasing temperature is 60±5° C., and the degreasing time is 300±5s.
3. The method for treating a magnesium alloy by forming a phosphorus-free and chromium-free film according to claim 1, characterized in that: The temperature of the activation expansion is 40±5°C and the time is 180±5s.
4. The method for treating a magnesium alloy by forming a phosphorus-free and chromium-free film according to claim 1, characterized in that: The temperature of the table adjustment is 65±5°C, and the time of a single table adjustment is 300±5s.
5. The method for forming a phosphorus-free and chromium-free film of a magnesium alloy according to claim 1, characterized in that: The temperature of the film formation is 45±5°C and the time is 240-300s.
Citation Information
Patent Citations
Magnesium alloy high-corrosion-resistant passivating agent, and passivation technology thereof
CN109385629A
